FIQH MAWARIS (SYARIAT KEWARISAN) DI INDONESIA - Sabri Deki Suwarna (Jurnal Syariah Hukum Islam, 2018)
The heirs are those who get the right to acquire the property of the deceased person who still has a blood relationship. The customary heir law includes rules and legal decisions pertaining to the process of continuation / transfer and transfer of material wealth and non material from generation to generation. Some of the tenets of inheritance are (1) heirs, (2) inheritance, and (3) heirs. The prevailing civil law in Indonesia still applies the provisions contained in the Civil Code / Civil Code (Burgerlijk Wetboek / BW). In the KUH Civil law heirs are part of the law of the property so that the legal arrangement is found in Book II of the Civil Code of the Law